2019
DOI: 10.1021/acs.iecr.9b00951
|View full text |Cite
|
Sign up to set email alerts
|

Role of Mineral Nutrients in Plant-Mediated Synthesis of Three-Dimensional Porous LaCoO3

Abstract: With the assistance of Cacumen Platycladi extract the facile synthesis of 3D porous LaCoO3 perovskite is reported at a lower calcination temperature of 500 °C as compared with the traditional citric acid method. The formation mechanism is carefully studied by investigating the different roles of organic and inorganic components in several plant extracts. Two key factors to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 53 publications
3
15
0
Order By: Relevance
“…The biosynthesized LaCoO 3 (Fig. S1(A-C)) shows the porous structure of stacked LaCoO 3 NPs with a relatively high surface area of 26.7 m 2 g À1 (Table 1), which is similar to those in our previous report [22]. In contrast, both PdO/LaCoO 3 (Fig.…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…The biosynthesized LaCoO 3 (Fig. S1(A-C)) shows the porous structure of stacked LaCoO 3 NPs with a relatively high surface area of 26.7 m 2 g À1 (Table 1), which is similar to those in our previous report [22]. In contrast, both PdO/LaCoO 3 (Fig.…”
Section: Resultssupporting
confidence: 85%
“…All of them only show characteristic diffraction peaks at 23.2°, 33.2°, 40.7°and 47.5°, which are assigned to a typical perovskite LaCoO 3 (JCPDS No. 48-0123), confirming the advantages of biosynthesis in producing perovskite-type structures at low calcination temperature [22]. XPS characterization was carried out to determine the state of Pd, since it was undetectable by XRD.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…Perovskite-type oxides applied in solar cells, catalytic materials, and optical sources are an emerging class of semiconducting materials exhibiting outstanding optoelectronic properties. Toniolo et al identified that Cu modified LaCoO 3 perovskites show desirable performance in the partial oxidation of methane to syngas. La 1– x Sr x FeO 3−δ which is effective for selective oxidation of ethane to ethylene or syngas demonstrates its immense potential in heterogeneous catalysis or even selective oxidation catalysis .…”
Section: Introductionmentioning
confidence: 99%